EFFICACY OF ATROPINE SULPHATE EYE DROPS IN CONTROLLING MYOPIA PROGRESSION: A REVIEW - Arcci Pradessatama; Umar Mardianto (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Myopia is major public health concern that has become increasingly common. Severe myopia has become one of the main causes of untreatable vision loss throughout the world, often due to its irreversible complications. Studies shows atropine can reduce myopia progression in children. Currently, there are no guidelines for the use of atropine specifically to control myopia progression. This study was made to review the efficacy of various atropine doses in controlling myopia progression. Methods: Literature searching was conducted in four online databases (PubMed, EBSCOhost, ScienceDirect, and Scopus. Search terms included were “Atropine” and “Myopia”. Validity was assessed using assessment tool from Cochrane. Efficacy was evaluated using myopia progression in spherical equivalent per year and axial lengthening per year. Results: Sixteen randomized controlled trial studies fulfilled our inclusion criteria and eligibility screening. Overall, atropine shows favorable results in spherical equivalent progression (D/year) compared to control, with SMD = -1.13, 95% CI (-0.58, -1.68). Less axial elongation (mm/year) was observed in atropine group, with SMD = -1.28, 95% CI (-0.18, -2.37). Atropine 0.01% concentration shows overall significantly better myopia progression and axial lengthening compared to control, with SMD = -0.76, 95% CI (-0.08, -1.44) and SMD = -0.63, 95% CI (-0.14, -1.12), respectively. Higher atropine doses showed larger effect sizes with higher occurrence of adverse effects. Conclusion: Atropine eye drops in various doses shows overall effective myopia control in spherical equivalent and axial lengthening. Atropine 0.01% has significant myopia progression inhibition with less adverse effects than higher doses.